ORAL CAVITY DYSBIOSIS UNDER THE DURABLE OPIOID ANALGESIC INFLUENCE IN EXPERIMENT - Фік, В.Б.; Федечко, Й.М.; Кривко, Ю.Я. (World of Medicine and Biology, 2015)
Experiments were hold on white male rats (20) aged 3,5-7,5 months. Experimental animals had been receiving opioid analgesic, derivative of morphine, once a week during 10 weeks. Bacteriological investigation included taking a culture and microscopic investigation of the smear. Мicrobiological investigations show that changes of bacterial population of the oral cavity which develop under the opioid intoxication can be characterized as dysbiosis. Results of our investigation which indicate the importance of the gram-positive microflora in development of inflammatory process in the oral cavity, in particular, importance of the St. aureus, which has wide range of adaptability characteristics and toxins with necrotic influence.
Keywords: oral cavity; opioid; microbiological investigation